Monitoring of Khapra Beetle in Jakarta, Tangerang, and Bekasi as Part of Khapra Beetle Free Area Maintenance Program in Indonesia - Permada, Johan; Witjaksono, Witjaksono; Wagiman, F. X. (Universitas Gadjah Mada, 2022)
Khapra beetle, Trogoderma granarium Evert (Coleoptera: Dermestidae) is the most important stored pest and was first discovered in Jakarta grain storages in 1972. Since then, quarantine procedures have been massively carried out to prevent khapra beetles to spread in Indonesia. In 2009, Indonesia has been declared as free area from Khapra beetle. However, Indonesia still import grain from non-Khapra beetle free countries and supervision must be carried out continuously to prevent Khapra beetle reinfestation. This survey was conducted at warehouses in five areas of Jakarta, Tangerang, and Bekasi from October 2016 to February 2017 with high risk due to its role as one of the main entry ports and storage of imported grains. Observation was done using probe sampling, direct observation and traps with attractant. Results showed that several insects were found from imported seeds in the surveyed area, but no Khapra beetles were found. It showed that non-Khapra free countries have implemented the required Sanitary Phytosanitary. In addition, it implies that survey methods using attractant traps could complement the probe sampling methods and direct observation that are currently used.